Usia Nikah dalam Perkawinan - Maotsiqon Azzam Ghiyatsulhaq; Putri Andini; Hafiz Gilman Abdul Aziz; Humaeroh Humaeroh (Jurnal Begawan Hukum (JBH), 2026)
Many marriages occur when a person is not old enough. Therefore, under Islamic law and Indonesian law the restriction of marriage age is a ijtihad stipulation. In this study we will discuss the boundaries of marriage age in a perspective on Islamic law and law in Indonesia. This type of study is literature research. From this study, the restriction on the marriage age of men and women is equivalent to 19 years old. To define marriage age, methodologs are based on mashlahah methods, thus not contradicting Nash and there is no specific Nash to be referenced for qiyas. The concept of mashlahah muris used to address the question of inclarity of marriage age. Maslahah murexplains that taking on a certain locality may be held asa metaphor for bataa marriage, although there is no detailed explanation in the Nash qur 'an. The so called conformity that is intended is an age limit for marriage established in Islamic law.